2017
DOI: 10.18203/2349-3291.ijcp20170702
|View full text |Cite
|
Sign up to set email alerts
|

Cord C-reactive protein as a marker for early onset neonatal sepsis children

Abstract: Background: Of the 2.8 million neonatal deaths, worldwide, 0.43 million is contributed by sepsis alone. The objective of this study was to determine the levels of umbilical cord C-reactive protein and assess the suitability of this test in diagnosing early onset sepsis in newborns born to mothers with no risk factors for intrapartum infection. To determine the influence of other factors such as parity, birth weight and mode of delivery on the levels of cord CRP.Methods: CRP levels in cord blood were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…Umbilical cord hs-CRP in present study had sensitivity and specificity of 51.6% and 68.8% respectively with diagnostic accuracy of 66.2%. Contrary to our study, study by Patrick et al [20] on 103 babies, out of which 12 were found to have sepsis found cord blood CRP to have sensitivity of 100% and specificity of 90%. The better diagnostic accuracy in this study could be because our study had a comparatively bigger sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Umbilical cord hs-CRP in present study had sensitivity and specificity of 51.6% and 68.8% respectively with diagnostic accuracy of 66.2%. Contrary to our study, study by Patrick et al [20] on 103 babies, out of which 12 were found to have sepsis found cord blood CRP to have sensitivity of 100% and specificity of 90%. The better diagnostic accuracy in this study could be because our study had a comparatively bigger sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…6 Cord CRP as an effective marker to predict EONS has been studied extensively with widely varied results. 14,15 When blood culture was considered as the standard cut off point, CRP was found to be an effective marker for neonatal sepsis with sensitivity ranging from 87-92%. 16,17 The discrepancy in the sensitivity of CRP in different studies is due to variations in diagnostic criteria, the time of onset of the infection (early or late) and different methods of CRP estimation (latex agglutination method or radio-immunodiffusion technique).…”
Section: Discussionmentioning
confidence: 99%